Chronic Recanalization of Dissection of the Distal Anterior Cerebral Artery: Case Report and Review of the Literature - Shuichiro Asano; Tetsuo Hara (Case Reports in Medicine)
The natural history of atraumatic idiopathic dissection of the distal anterior cerebral artery is still unclear. We present a 38-year-old man who had dissection of the left A2 segment of this vessel associated with subintimal hematoma and infarction. Because of complete stroke in acute stage, he did not undergo surgery. About three months later, administration of aspirin (100 mg/day) was started. At nine months, magnetic resonance angiography revealed complete recanalization of the A2 dissection. To assess the outcome of dissection, we should observe the patient for at least one year.